Self-Assembly of Pseudo Isocyanine Chloride in the Presence of Attractive Polyethylene Glycol Crowders - Koch, Leon; Rajput, Satyendra; Richter, Antonio; König, Benedikt; Nayar, Divya; Ebbinghaus, Simon; Huber, Klaus (The Journal of Physical Chemistry B)

Analysis of the Growth Mechanism of Eumelanin Particles by Time-Resolved Static and Dynamic Light Scattering - Kollmann, Fabian; Büngeler, Anne; Splett, Miriam; Strube, Oliver I.; Huber, Klaus (Biomacromolecules)

Coil dimensions of macromolecules in the presence of crowding colloids: Impact of crowder size - Huber, Klaus; Martens, C.M.; Tuinier, R. (Journal of Colloid and Interface Science)

Philosophie und Ethik in der Lehrerinnen- und Lehrerbildung. Grundlagen und Perspektiven - Albus, Vanessa (Handbuch Lehrerinnen- und Lehrerbildung)

Rezension: La peinture murale en Alsace au coeur du Rhin supérieur du Moyen Âge à nos jours / Die Wandmalerei im Elsass im Herzen des Oberrheins vom Mittelalter bis heute - Heinrichs, Ulrike (The Burlington Magazine)

Monoton erreichbarer Delaunaygraph - Werner, Felix

Gott, heilger Schöpfer aller Stern (EG 3). Zum 500. Todestag von Thomas Müntzer (1489-1525) - Schroeter-Wittke, Harald (Praktische Theologie)

A 50 Gbps Reference-less NRZ Full-rate Bang-Bang CDR with Automatic Frequency Acquisition in 130 nm SiGe:C BiCMOS Technology - Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Scheytt, J. Christoph (IEEE Nordic Circuits and Systems Conference (NORCAS))

A 128 GS/s 2x Time-Interleaved Track and Hold Amplifier in 130nm SiGe BiCMOS - Weizel, Maxim; Malavalli Nagaraju, Harshan Gowda; Scheytt, J. Christoph (2025 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

Verilator and FireSim RTL Simulations on a HPC Cluster: A Comparative Case Study - Hannemann, Kai Arne; Bütün, Hüseyin Berke; Müller, Wolfgang; Scheytt, J. Christoph (MBMV 2025 - 28. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen)

Design and Integration of Intra-Process Communication for ROS 2 into ReconROS - Bengaluru Amarnath, Prajwal

„Bis in Kirche und Schule hinein. Irmtraud Fischers Schreiben und Lehren weitergedacht“. Rezension von Frauen, die sich einmischen. Biblisch-politische Lektüren, Festgabe für Irmtraud Fischer aus Anlass ihres 65. Geburtstages. - Bergmann, Claudia Dorit (Praktische Theologie)

Rezension zu: „The Bible in Folklore Worldwide. Volume 2: A Handbook of Biblical Reception in Folklores of Africa, Asia, Oceania, and the Americas” - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik)

Rezension zu: „Vielleicht...Ein hebräisches Modalwörtchen und seine Bedeutung für eine Theologie der Hoffnung” - Bergmann, Claudia Dorit (Theologische Literaturzeitung)

'Look to Abraham and Sarah' - Bergmann, Claudia Dorit; Latt, May May (Imitating Abraham: Ritual and Exemplarity in Jewish and Christian Contexts)

Circular product design: a literature-based identification of challenges from the perspective of product designers - Jagnow, Jan; Stöhr, Bernd; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: The importance of the circular economy as an alternative to today’s prevailing linear economy is recognised in both industry and research. Product designers are having a major influence on this transition by adapting the characteristics of physical products in the early phases of the product development process. However, most products follow a linear approach and are far from being circular. This paper aims to identify the challenges that product designers face when designing circular products. Building on a developed understanding of related terms in circular product design, an exploratory literature review is conducted. The results help to gain an overview and understanding of the challenges that need to be addressed. Therefore, further research directions are derived to support the transition from linear to circular products in the long term.

Effective management support for design: towards a model of managerial competence - Stöhr, Bernd; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: Well-designed products are crucial to a company's business success. Management support is a critical success factor in ensuring that design-related aspects are given appropriate attention during product development. Despite the importance of management, the literature doesn't provide a clear picture of what characterizes a competent manager in product design. This gap impedes competence development and explains why organizations struggle to leverage the benefits of well-designed products. This research aims to address this gap by synthesizing important findings from the literature into a model of managerial competence. The model provides initial insight into the individual competencies managers need to meet their responsibility for good product design in organizations.

„Ins Offene“. Die räumliche Verlagerung jüdischer Mahlrituale in antiken jüdischen Texten und modernen Krisenzeiten. - Bergmann, Claudia Dorit (Grenzgänge: Beiträge für eine Liturgiewissenschaft zwischen akademischem Diskurs, pluraler Kultur und kirchlichem Leben. Festschrift für Benedikt Kranemann.)

Crime Fever. Colonial Pathologies in Émile Zola’s Thérèse Raquin (1867) - Schlieper, Hendrik (Bodies, Remedies, Policies. From Early Modern Chronicles of the Indies to Covid-19 Narratives)

Labern als Beruf? Schriftsteller-Intellektuelle im Podcast - Heise, Tillmann (Literatur und Podcast. Inszenierungsformen – Rezeptionsmodelle – Wissenskommunikation)